Integrated analysis identifying new lncRNA markers revealed in ceRNA network for tumor recurrence in papillary thyroid carcinoma and build of nomogram. Issue 12 (4th July 2019) - Chen, Fangyao; Li, Zhe; Deng, Changyu; Yan, Hong
Abstract: Object: The risk of tumor recurrence is currently the focus of clinical attention in the treatment of papillary thyroid carcinoma (PTC). This study focuses on the identification of novel prognostic long noncoding RNA (lncRNA) signatures for tumor recurrence in PTC. Method: RNA sequencing profiling of patients with PTC was obtained from the TCGA and Gene Expression Omnibus databases. Differently expressed lncRNA, microRNA (miRNA), and messenger RNA (mRNA) signatures between patients with and without tumor recurrence were selected. The lncRNA‐miRNA‐mRNA competing endogenous RNA (ceRNA) network for tumor recurrence in PTC was constructed to identify lncRNAs associated with tumor relapse in papillary carcinoma. Functional enrichment analysis was performed. Adjusted odds ratios were estimated to identify candidate prognostic lncRNAs considering clinical covariates. Validation analysis was conducted. Nomogram was built based on the verified prognostic lncRNAs and clinical features. Results: The lncRNA‐miRNA‐mRNA ceRNA network for tumor recurrence in PTC was constructed. Functional enrichment analysis suggested that the identified lncRNAs were associated with PTC. Adjusted odds ratios indicated that 5 of the 16 selected lncRNAs were candidate biomarkers predicting tumor recurrence of thyroid carcinoma. Among which, TTTY10 was verified as novel prognostic markers in validation analysis. Nomogram was built based on the newly identified lncRNA biomarker and clinical covariates. Conclusion: In this study, lncRNA TTTY10 was identified as potential novel prognostic markers predicting tumor recurrence in PTC. It may provide useful information for future molecular and cohort studies focusing on the prognosis of PTC. Abstract : This study aimed at the identification of the novel prognostic lncRNA signatures for the prediction of tumor recurrence in papillary thyroid carcinoma (PTC). As a result, 15 lncRNAs, 11 miRNAs, and 36 mRNAs interacted in the lncRNA‐miRNA0mRNA ceRNA network, and three lncRNAs were selected through the ceRNA network to be as novel prognostic predictor for tumor recurrence of papillary thyroid carcinoma with stage and extension status as covariates.